A gold nanorod-based plasmonic platform for multi-logic operation and detection. (6th December 2018) - Li, Tong; Bi, Junmin; Ren, Hang; Ling, Rui; Zhang, Chenling; Wu, Zhenglong; Qin, Weidong; Jiao, Peng
Abstract: A multi-logic gate platform was designed based on morphological changes of gold nanorods (AuNRs) resulted from the iodine-mediated etching. By utilizing the anti-etching effects of mercapto compounds and Au-Hg amalgams as well as the etch-promoting effect of Cu 2+, we successfully built five logic gates, namely, AND, NOR, XNOR, YES and IMPLY, along with a three-input combinational logic gate XNOR-IMPLY. The platform was versatile and easy to use, did not require complex surface modification or separation/purification steps as the conventional AuNR-based logic gates did. The logic operations, accompanied by distinct color changes, enabled multi-task detection by naked-eye for 'have' or 'none' discrimination or highly sensitive and selective analysis by spectroscopy with wide linear ranges.